0.1C–11Mn medium manganese steel treated by quenching and tempering process. Issue 17 (22nd November 2022) - Zhao, Yan; Yang, Dengcui; Yin, Xiandong; Zhiying,; , Mo; Wang, Shuai; Zhao, WeiYan; Chu, Xiaohong; Zhao, Zhengzhi
Abstract : In this work, we developed a third-generation automobile steel with high strength and elongation of 0.1C–11Mn medium manganese steel using a simple quenching and low-temperature tempering heat treatment procedure. At different austenitisation temperatures, the microstructure and mechanical properties of manganese steel were examined. The microstructure included tempered martensite (TM), austenite, and ultra-fine-grained ferrite. The steel achieved the highest strength and elongation of 39.1GPa·% when it was quenched at 630°C for 10 min and tempered at 450°C for 5 min. In conclusion, dislocation strengthening was the primary factor to increase yield strength. At 630°C, the steel achieved its best mechanical properties because of a higher austenite stability, work-hardening capability, and synergistic impact of ultra-fine-grained ferrite and martensite.